How to draw a novel - Solares, Martín, 1970- (Grove Press, an imprint of Grove Atlantic, 2023)
A meditation on literary craft that muses on how and why novels communicate with readers. Shows how fiction operates, exploring the conventions of form, the novel as a house that one must build brick by brick, and the objects and characters that build out the world of the novel. The author uses his own line drawings to portray the ebb and flow of novels. He considers how writers invent or discover their characters, the importance or unimportance of place, and the myriad shapes the novel may take. An important contribution to the study of craft and fiction.